Dinamika Pelaksanaan Eksekusi Putusan Pengadilan Perdata Yang Telah Memiliki Kekuatan Hukum Tetap - Meiddy Dwi Darmawan; Sidi Ahyar Wiraguna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Civil court decisions that have obtained permanent legal force in Indonesia often fail to be executed effectively, creating a gap between normative legal certainty and practical implementation. This study aims to analyze juridical and non juridical obstacles to the execution of civil judgments and to formulate an ideal legal construction that strengthens procedural certainty and institutional accountability. The research employs normative legal research using statutory, conceptual, and limited case approaches, with a population consisting of all regulations, court policies, and scholarly works on civil judgment execution in Indonesia. Samples of legal materials are selected purposively based on their relevance to juridical and non juridical barriers and to the design of an ideal execution model. Data are collected through systematic literature study and analyzed using content analysis and qualitative prescriptive techniques to categorize norms, doctrines, and empirical findings into coherent analytical themes. The results show that weaknesses in procedural regulation, unclear operative parts of judgments, lack of asset tracing mechanisms, social resistance, limited court resources, and weak inter agency coordination jointly undermine the effectiveness of execution. The conclusion is that a reformed execution system requires simultaneous normative, institutional, and socio cultural reforms anchored in a five element conceptual model: executable judgment, procedural certainty, institutional safeguard, social compliance, and judicial accountability.